Quality improvement through collaboration: the National Pediatric Quality improvement Collaborative initiative. Issue 5 (October 2015) - Clauss, Sarah B.; Anderson, Jeffrey B.; Lannon, Carole; Lihn, Stacey; Beekman, Robert H.; Kugler, John D.; Martin, Gerard R.
Abstract : Purpose of review: The National Pediatric Quality Improvement Collaborative (NPCQIC) was established to improve outcomes and quality of life in children with hypoplastic left heart syndrome and other single ventricle lesions requiring a Norwood operation. The NPCQIC consists of a network of providers and families collecting longitudinal data, conducting research, and using quality improvement science to decrease variations in care, develop and spread best practices, and decrease mortality. Recent findings: Initial descriptive investigation of the collaborative data found interstage care process variations, different surgical strategies, diverse feeding practices, and variable ICU approaches between centers and within sites. Analysis and evaluation of these practice variations have allowed centers to learn from each other and implement change to improve processes. There has been an improvement in performance measures and most importantly, a 39.7% reduction in mortality. Summary: The NPCQIC has shown, in a rare disease such as hypoplastic left heart syndrome that a network based on multicenter collaboration, patient (parent) engagement, and quality improvement science can facilitate change in practices and improvement in outcomes.